Environmental Sensitivity Peserta Didik Terhadap Citizenship Behavior Yang Dimediasi Oleh Intention To Act Peserta Didik - Siti Gautami Cantika Putri; I Made Putrawan; Refirman Djamahar (IJEEM - Indonesian Journal of Environmental Education and Management, 2022)
The environment and humans have a reciprocal and interdependent relationship. There is a reciprocal relationship between the environment and humans resulting in environmental problems that will affect the environment and other living things. The main cause of environmental problems is the waning of one's concern and wise behavior towards the environment. This study aims to determine the effect of students environmental sensitivity on citizenship behavior mediated by students intention to act related to the environment. The research method used is a survey method through a causal study which is analyzed by path analysis. The research was conducted at SMAN 14 Jakarta in the odd semester of the 2021/2022 academic year. The result of the calculation of the reliability coefficient of the citizenship behavior instrument is 0.896, environmental sensitivity is 0.909, and the intention to act is 0.916. The results of this study indicate that environmental sensitivity has a direct effect on intention to act significantly, intention to act has a significant direct effect on citizenship behavior, environmental sensitivity has a direct effect on citizenship behavior significantly, and environmental sensitivity has an indirect effect on citizenship behavior through intention to act. act. So that intention to act can mediate between environmental sensitivity and citizenship behavior of students.